A new tribe, two new genera and three new species of Cypridopsinae (Crustacea, Ostracoda, Cyprididae) from Brazil - Almeida, Nadiny Martins; Higuti, Janet; Ferreira, Vitor Góis; Martens, Koen (European Journal of Taxonomy, 2021)
We describe one new tribe, two new genera and three new species of the subfamily Cypridopsinae Kaufmann, 1900 from Brazilian floodplains. Brasilodopsis gen. nov. belongs in the nominal tribe Cypridopsini, and both new species in this new genus were found in both sexual and asexual populations. Brasilodopsis baiabonita gen. et sp. nov. has a wide distribution and was found in three of the four major Brazilian floodplains. Brasilodopsis amazonica gen. et sp. nov. was recorded only from the Amazon floodplain. Brasilodopsis baiabonita gen. et sp. nov. has a subtriangular shape in lateral view, whereas Brasilodopsis amazonica gen. et sp. nov. is more elongated and has more rounded dorsal margins in both valves, as well as more pronounced external valve ornamentation, consisting of rimmed pores in shallow pits. Paranadopsis reducta gen. et sp. nov. was found in asexual populations in the Upper Paraná River floodplain only and differs from other Cypridopsinae in the more elongated carapace, an A1 with strongly reduced chaetotaxy (hence the specific name) and the total absence of caudal rami in females. Because of these strong reductions in valve and limb morphology, Paranadopsini trib. nov. is created within the Cypridopsinae for this intriguing new genus and species.